HERMENEUTICS OF EARNING MANAGEMENT: BETWEEN PRESSURE AND OPPORTUNITY - Subadriyah (International Conference on Industrial Revolution for Polytechnic Education, 2019)
The purpose of this study was to find out and understand the informants which included internal auditors and staff on the practice of earnings management carried out by managers of savings and loan cooperatives (KSP). This research was conducted at A and B savings and loan cooperatives in Jepara. Cooperatives are chosen with very high NPLs and those with NPLs below the standard. Research informants were chosen purposively based on individuals who have been long enough and intensively integrated into their fields of work. The analysis in this study is an interpretive or hermeneutic approach. The way this approach works is by interpreting the language through grammatical and psychological interpretation. The results obtained show different information in earnings management practices. Opportunities in utilizing the application of generally accepted accounting principles are the things that underlie earnings management. The informant stated that earnings management cannot be considered as profit manipulation as long as the process is carried out in the notification of accounting standards. The accounting staff said his opinion that earnings management behavior could not be considered as corrupt unless the behavior was not carried out in accounting standards.